2018
DOI: 10.1007/s11523-017-0548-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Driven Therapy in Metastatic Gastric and Esophageal Cancer: Real-Life Clinical Experience

Abstract: BackgroundPrecision treatment of cancer uses biomarker-driven therapy to individualize and optimize patient care.ObjectiveTo evaluate real-life clinical experience with biomarker-driven therapy in metastatic gastric and esophageal cancer in Israel.Patients and MethodsThis multicenter retrospective cohort study included patients with metastatic gastric or esophageal cancer who were treated in the participating institutions and underwent biomarker-driven therapy. Treatment was considered to have a benefit if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…TOP2A controls topological states of DNA, a crucial role for proper segregation of daughter chromosomes during mitosis and meiosis [ 50 ]. One clinical study suggested that high TOP2A could serve as a biomarker driving medical therapy [ 51 ]. Another study showed that the knockdown of the long noncoding RNA (lncRNA) DDX11-AS1 reversed paclitaxel (PTX) resistance by means of inhibiting the expression level of TOP2A [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…TOP2A controls topological states of DNA, a crucial role for proper segregation of daughter chromosomes during mitosis and meiosis [ 50 ]. One clinical study suggested that high TOP2A could serve as a biomarker driving medical therapy [ 51 ]. Another study showed that the knockdown of the long noncoding RNA (lncRNA) DDX11-AS1 reversed paclitaxel (PTX) resistance by means of inhibiting the expression level of TOP2A [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following this pivotal study, the CMI MMP approach was incorporated into clinical practice, and reports describing additional analyses focusing on the utility of this approach were published/presented. Table 2 summarizes the Von Hoff study as well as 10 subsequent studies conducted worldwide (US, Austria, Australia, Israel, Lebanon, and Egypt) [13][14][15][16][17][18][19][20][21][22][23] . Some of these studies investigated advanced disease in specific tumor types such as gastric/esophageal 14 , pancreatic/pancreaticobiliary 15,16 , breast 17 , and salivary glands cancer 18 , whereas other studies included a variety of refractory solid cancers including rare tumors [19][20][21][22][23] .…”
Section: Studies Exploring the Clinical Utility Of Mmpmentioning
confidence: 99%
“…All the studies reported on clinical benefit. In 7 studies (involving a total of 218 evaluable patients) the PFS ratio endpoint was used, and the clinical benefit rate ranged from 27% to 59.5% [13][14][15]17,19,22,23 . In the remaining 4 studies (involving a total of 127 evaluable patients), other outcome measures were used such as response rate (complete response [CR] rate plus partial response [PR] rate), disease control rate (CR plus PR plus stable disease [SD] rate), and 1-year survival rate.…”
Section: Studies Exploring the Clinical Utility Of Mmpmentioning
confidence: 99%
See 1 more Smart Citation
“…If the observed PFS ratio was greater than 1.3 (indicating a 30% increase in PFS with profiling-guided treatment), the patient was considered to have clinical benefit. Nine other physician-led evaluations of CMI have been conducted globally in a variety of solid tumours [21][22][23][24][25][26][27][28]. The definition of clinical benefit differed between studies and includedPFS ratio as described by von Hoff to more traditional endpoints such as disease control rate, response or overall survival greater than 6 months.…”
Section: Clinical Evidence Supporting the Use Of CMImentioning
confidence: 99%